The Hepatoprotective Effects of Basil Leaf (Ocimum sanctum L.) Extract on Paracetamol Induced Liver Damage in Male Rat - Panggabean, Ronaldo; Nofita; Ade Maria Ulfa (Biomedical Journal of Indonesia, 2021)
Basil leaf have antioxidants such as flavonoids, so it is thought to have a hepatoprotective effect. This study aims to investigate the effect of basil leaf extract on SGOT and SGPT levels in male rats induced by paracetamol. Basil leaf extract was carried out by the percolation method using ethyl acetate solvent, Some 20 male sprague dawley rats were randomly divided into 5 groups. Basil leaf extract (400 mg/kgBB and 600 mg/kgBB) and sylimarin (100 mg/kgBB) were carried out every day for 28 days, paracetamol was induced 24 hours after giving the last day of basil leaf extract. The parameters measured were SGOT and SGPT level to assess the effect of basil leaf extract on liver damage caused by paracetamol. The results showed that basil leaf extract (400 mg/kgBB dan 600 mg/kgBB) showed that the activities of SGOT and SGPT levels were statistically significant (p<0,05) to negative control. Basil leaf extract shows the effect of hepatoprotector on liver induced by paracetamol, however the effect given was not able to equate with positive control.